X-ray and thermal analysis of high-capacity iron- and nickel-containing lithium-rich layered-oxide cathode treated by carbothermal reduction. (10th November 2018) - Narita, Kaoru; Yuge, Ryota; Kuroshima, Sadanori; Tabuchi, Mitsuharu; Doumae, Kyosuke; Shibuya, Hideka; Tamura, Noriyuki; Tsuji, Masayoshi
Abstract: A high-capacity iron- and nickel-substituted Li 2 MnO 3 cathode [i.e., Li 1.26 Fe 0.11 Ni 0.11 Mn 0.52 O 2 (LFNM)] treated by carbothermal reduction was analyzed, and the results clarified that it has both high capacity and high safety levels. X-ray analysis of a reduced LFNM (R-LFNM) cathode clarified the following. Migration of transition metals in the lattice as a result of the carbothermal reduction stabilizes the layered lattice structure, which prevents lattice shrinkage during charging and enhances charge compensation. As a result, more lithium ions can return to the cathode during discharging; namely, the irreversible capacity of the cathode decreases. Thermal stability of the R-LFNM cathode was evaluated by differential scanning calorimetry (DSC), and the results show that the total heat evolved from the R-LFNM cathode remains at a lower level compared with that of other cobalt- and nickel-containing Li 2 MnO 3 cathodes. An analysis of the lattice structure reveals that low exothermic heat from the charged R-LFNM cathode results from the distinctive property of its crystal lattice changing from layered to thermally stable spinel during charging.